1994
DOI: 10.1111/j.1348-0421.1994.tb01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Spirosin of Yersinia enterocolitica and Analysis of the Localization of Spirosome by Use of Them

Abstract: Two hybridomas producing monoclonal antibodies (MAbs) were prepared by fusing myeloma cells (Sp2/0-Ag14) with mouse spleen cells immunized with purified spirosin from Yersinia enterocolitica SYT-11-72 (YE72). The antibodies produced by them were designated MAbs-S5 and S27. They were IgG2a and IgGi, respectively, both with k light chains. MAbs-S5 and S27 reacted specifically with spirosin from YE72. On Western blotting after limited proteolysis with Staphylococcus aureus V8 protease, YE72 spirosin revealed pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The 95 kDa protein band stained with Coomassie Brilliant Blue R250 was cut off and analyzed for the sequence on a model HPG1005A Protein Sequencing System (Hewlett-Packard, Inc., Palo Alto, CA, USA). However, the N-terminal amino acid sequence of spirosin from L. reuteri DSM 20016 could not be determined, probably because of N-acylation as in the case of L. brevis (Yamato et al, 1994). Since the amino acid sequence from L. acidophilus ATCC 9857 could not be detected either, N-acylation seems to be a chemical feature common to the Lactobacillus spirosins.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The 95 kDa protein band stained with Coomassie Brilliant Blue R250 was cut off and analyzed for the sequence on a model HPG1005A Protein Sequencing System (Hewlett-Packard, Inc., Palo Alto, CA, USA). However, the N-terminal amino acid sequence of spirosin from L. reuteri DSM 20016 could not be determined, probably because of N-acylation as in the case of L. brevis (Yamato et al, 1994). Since the amino acid sequence from L. acidophilus ATCC 9857 could not be detected either, N-acylation seems to be a chemical feature common to the Lactobacillus spirosins.…”
mentioning
confidence: 80%
“…The spirosome from Lactobacillus and Enterobacteriaceae is composed of 95 kDa protein subunits called spirosin (Ueki et al, 1982;Yamato et al, 1995). There have been many reports on morphological, biochemical and immunochemical studies of spirosome as quoted in our previous papers (Yamato et al, 1994(Yamato et al, , 1995. Though some functional aspects of spirosome have been described so far Matayoshi et al, 1989), its function is not yet well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper (12), we described the preparation of a monoclonal antibody (MAb-S5) specific for spirosin of Yersinia enterocolitica SYT- and the localization of spirosome in the bacterial cytoplasm as well. Recently, Kessler et al have shown that pyruvate-formate-lyase-deactivase and acetyl-CoA reductase of E. coli reside on a polymeric protein particle encoded by adhE which they speculated might be identical to spirosome (7).…”
mentioning
confidence: 99%
“…Imamura et al have demonstrated that a cytoplasmic protein designated p100-A of E. coli has a spirosome-like structure and that the N-terminal amino acid sequence of p100-A is identical to that of alcohol dehydrogenase (ADH) encoded by adhE gene (2). The identity of the N-terminal amino acid sequence of spirosin to that of ADH in E. coli (1,12) prompted us to suggest that spirosin is probably ADH. Morphological analysis in electron microscopy also supported the identity of the two substances (2,7).…”
mentioning
confidence: 99%